2020
DOI: 10.1371/journal.pone.0236713
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence determinants in coagulase-negative staphylococci isolated mainly from preterm neonates

Abstract: Coagulase-negative staphylococci (CoNS) are the most common isolates from blood culture in neonates resulting in high mortality and morbidity. This study investigated CoNS obtained from blood cultures of neonates for antibiotic resistance and virulence factors, and possible association with inflammatory response (C-reactive protein). A total of 93 CoNS isolates were collected from 76 blood cultures of neonates at the Maternity hospital in Kuwait in a six-month period and investigated for susceptibility to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
6
16
0
Order By: Relevance
“…A single clone that has been circulating from 2009 to 2012 might be associated with an outbreak of S. capitis involving patients with a positive blood culture and a wound infection. Staphylococcus capitis is not a common nosocomial pathogen and is rarely found in the microbiota of tested patients [ 43 ]. Nevertheless, this species is endemic in some neonatal units and has been associated with bloodstream infections [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single clone that has been circulating from 2009 to 2012 might be associated with an outbreak of S. capitis involving patients with a positive blood culture and a wound infection. Staphylococcus capitis is not a common nosocomial pathogen and is rarely found in the microbiota of tested patients [ 43 ]. Nevertheless, this species is endemic in some neonatal units and has been associated with bloodstream infections [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more than half of the isolates were MDR, as has been observed in other studies carried out in Brazil, Colombia, and Kuwait. Those studies reported MDR S. epidermidis on “high-touch” surfaces, in NICU environmental air, and in clinical samples (52.7%, 33.9%, and 61.8%, respectively) [ 28 , 29 , 30 ]. Our study revealed the presence of S. epidermidis MDR in much higher percentages (81%), 72.7% of inanimate surfaces, 68.8% of air, and 100% of clinical isolates, which alerts us to the need for urgent measures to minimize the risk of proliferation of these microorganisms in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Among S. epidermidis isolates from neonatal blood, the vast majority (85–90%) are capable of producing biofilm [ 161 , 162 ]. However, the rate of biofilm production and the presence of icaADB and altE in S. epidermidis isolates from neonatal bloodstream infection (BSI) was comparable to commensal S. epidermidis isolates from neonatal nares [ 149 ].…”
Section: Genetic Determinants Of Virulence In Commensal and Invasive S Epidermidismentioning
confidence: 99%